Damage to the Optic Radiation in Patients With Mild Traumatic Brain Injury. Issue 3 (September 2015) - Jang, Sung Ho; Seo, Jeong Pyo
Abstract : Background: There are known limitations of conventional computed tomography and magnetic resonance imaging in detecting neural injury in patients with mild traumatic brain injury (TBI). Diffusion tensor imaging (DTI) provides a method to further assess cerebral injury in this patient population. We report 2 patients with mild TBI who showed injury of the optic radiation (OR) as demonstrated by DTI. Method: Two patients who complained of visual field loss after mild TBI and 9 age-matched normal control subjects were recruited for this study. Peripheral field defects were detected with automated perimetry in both patients. Results: Regarding the configuration of OR, the total volume of OR was decreased in the right OR of both patients compared with controls; in contrast, the left ORs were divided into 2 parts in both patients. The voxel numbers of both ORs in both patients were more than 2 standard deviations lower than that of normal control subjects. The apparent diffusion coefficient value of the right OR in patient 2 was more than 2 standard deviations higher than that of normal controls. Conclusions: We demonstrated injury of the OR using DTI in 2 patients who showed visual field defects after mild TBI.